Prolaps Rekti Komplit pada Pasien dengan Kecurigaan Benign Prostatic Hyperplasia: Laporan Kasus - Fatinah Zhohiroh, Jannah; Fathurrahman, Yusmaidi (CV. Jasa Sukses Abadi, 2026)
Rectal prolapse is a condition characterized by the protrusion of the full thickness of the rectal wall through the anus due to weakness of the pelvic floor supporting structures, which is chronic and progressive in nature. Repeated increases in intra-abdominal pressure, such as in chronic constipation and lower urinary tract disorders, play a role in its pathogenesis. We report a case of a 55-year-old male presenting with a protruding anal mass that could not be manually reduced for 8 hours prior to admission, with a history of progressively worsening prolapse over approximately ±10 years. Complaint accompanied by chronic constipation, with hard, infrequent bowel movements and habitual excessive straining during defecation and lower urinary tract symptoms suggestive of benign prostatic hyperplasia (BPH). Physical examination revealed a cylindrical prolapsed mass with a central orifice, characteristic of complete rectal prolapse. No signs of acute complications or significant systemic abnormalities were found on supporting investigations. The patient underwent surgical management with suture rectopexy as the definitive treatment combined with the Thiersch procedure. This combined approach was selected due to the long-standing, large prolapse and the suspected sphincter weakness, aiming to provide anatomical stabilization along with additional mechanical support to reduce the risk of recurrence. Postoperatively, the patient showed clinical improvement without complications. This case highlights the importance of identifying factors that increase intra-abdominal pressure and considering combined surgical approaches in managing complete rectal prolapse to achieve optimal clinical outcomes.